123 The Incidence of neurological symptoms in patients with traumatic brain injuries and return to work. Issue 6 (27th May 2022) - McHattie, Andrew; Jenkins, Peter
Abstract : Objectives: To investigate: 1) The incidence of neurological symptoms in a traumatic brain injury (TBI) clinic; 2) The relationship between symptoms and injury severity; 3) The cause of persistent symptoms; 4) The factors preventing return-to-work Background: Persistent symptoms after even a mild TBI are common. The diagnosis of post-concussion syndrome is often used in this situation with the assumption that symptoms will self-resolve. However, this is frequently not the case and neurological and neuropsychiatric diagnoses including migraine, BPPV and anxiety often underlie these persistent symptoms. Methods: 66 patients with a range of TBI severities were evaluated in a dedicated TBI clinic. Data was collected on the incidence of neurological symptoms, symptom persistence, and return-to-work rates. Results: There was a high incidence of neurological diagnoses, particularly migraine and BPPV. Both were associated with an increased odds ratio of failure to return-to-work within 30 days. Migraine, in particular, was a common cause of persistent symptoms. Conclusions: Neurological diagnoses are common causes of persistent symptoms post-TBI. Their incidence is associated with a failure to return-to-work. Post-concussion syndrome is an unhelpful diagnostic label as it incorrectly assumes self-resolution of symptoms; instead, diagnostic clarity for each individual is necessary to help guide treatment. andrewwilliam.mchattie@nhs.net